The long tail of molecular alterations in non-small cell lung cancer: a single-institution experience of next-generation sequencing in clinical molecular diagnostics. Issue 9 (13th March 2018) - Fumagalli, Caterina; Vacirca, Davide; Rappa, Alessandra; Passaro, Antonio; Guarize, Juliana; Rafaniello Raviele, Paola; de Marinis, Filippo; Spaggiari, Lorenzo; Casadio, Chiara; Viale, Giuseppe; Barberis, Massimo; Guerini-Rocco, Elena
Abstract : Background: Molecular profiling of advanced non-small cell lung cancers (NSCLC) is essential to identify patients who may benefit from targeted treatments. In the last years, the number of potentially actionable molecular alterations has rapidly increased. Next-generation sequencing allows for the analysis of multiple genes simultaneously. Aims: To evaluate the feasibility and the throughput of next-generation sequencing in clinical molecular diagnostics of advanced NSCLC. Methods: A single-institution cohort of 535 non-squamous NSCLC was profiled using a next-generation sequencing panel targeting 22 actionable and cancer-related genes. Results: 441 non-squamous NSCLC (82.4%) harboured at least one gene alteration, including 340 cases (63.6%) with clinically relevant molecular aberrations. Mutations have been detected in all but one gene ( FGFR1 ) of the panel. Recurrent alterations were observed in KRAS, TP53, EGFR, STK11 and MET genes, whereas the remaining genes were mutated in <5% of the cases. Concurrent mutations were detected in 183 tumours (34.2%), mostly impairing KRAS or EGFR in association with TP53 alterations. Conclusions: The study highlights the feasibility of targeted next-generation sequencing in clinical setting. The majority of NSCLC harboured mutations in clinically relevant genes, thus identifying patients who might benefit from different targeted therapies.